How effective is indocyanine green (ICG) in localization of malignant pulmonary nodules? A systematic review and meta-analysis - Gkikas, Andreas; Lampridis, Savvas; Patrini, Davide; Kestenholz, Peter B.; Scarci, Marco; Minervini, Fabrizio (Frontiers in Surgery, 2022)
Background Video-Assisted and Robotic-Assisted techniques become constantly more prominent practice in thoracic surgery for lung cancer. Furthermore, the increased frequency in detection of small lung cancers makes the intra-operative identification of these cancers even more challenging. Indocyanine Green (ICG) is one of the most commonly used dyes that assists surgeons identify small lung cancers intra-operatively. Our study aimed to evaluate the effectiveness and safety of ICG in lung cancer detection. Methods We performed a systematic review of the literature by screening the databases of MEDLINE, EMBASE, CENTRAL and Scopus until 30th April 2022 and the first 300 articles of Google Scholar for any suitable grey literature. We included any study that investigated the effectiveness of ICG in lung cancer detection. We excluded studies that explored the use of ICG only in identification of intersegmental planes, lymph node mapping, case reports and non-English articles. We aimed to perform a meta-analysis on test accuracy studies using hierarchical summary receiver operating characteristic (HSROC) and the bivariate random-effects models. Each study was assessed for Risk of Bias (RoB) and Applicability using the QUADAS-2 tool. Results We found 30 eligible studies that included a total of 1776 patients who underwent ICG localization of pulmonary nodules. We identified three ICG localization techniques: CT-guided, endobronchial and intravenous. From the 30 studies, 13 investigated CT-guided localization, 12 explored an endobronchial method while 8 studies administered ICG intravenously The median reported success rate was 94.3% (IQR: 91.4% - 100%) and 98.3% (IQR: 94% - 100%) for the first two techniques respectively. Intravenous ICG lung cancer localization showed Sensitivity of 88% (95% CI: 59% - 0.97%) and Specificity of 25% (95% CI: 0.04% - 0.74%). There were 15.2% (150/989) patients who experienced complications from CT guided ICG localization. No ICG-related complications were reported in endobronchial or intravenous techniques. Conclusion Our study provides a comprehensive review of the literature on ICG localization techniques for lung cancer. Current evidence suggests that ICG is boh effective and safe. Further prospective research with standardized protocols across multiple thoracic units is required in order to accurately validate these findings.